Factor influencing the Islamic credit cards holder selection / Dhaim Abd Rahman - Abd Rahman, Dhaim (Faculty of Business and Management, 2011)
The study was conducted to find out the relationship between independent and dependent variable. The independent variables chosen are service quality and religiosity satisfaction. The selection of Islamic credit cards (ICC) is the dependent variable. When the primary data is used in this study, therefore a SPSS system was to find a result whether to accept or reject the hypothesis. The method of this study is the regression analysis. The finding has been interpreted base on the correlation, coefficient correlation, F-statistic and T-statistic. The data that been used in this study was collected for the period of January until March 2011. Base on the result, it was summarized that both service quality and religiosity satisfaction has a significant relationship toward selection of ICC.